Diagnostic Approach for Monitoring Hydroclimatic Conditions Related to Emergence of West Nile Virus in West Virginia - Jutla, Antarpreet; Huq, Anwar; Colwell, Rita R. (Frontiers in Public Health, 2015)
West Nile virus (WNV), mosquito-borne and water-based, is increasingly a global threat to public health. Since its appearance in the northeastern United States in 1999, WNV has since been reported in several states in the continental United States. The objective of this study is to highlight the utility of satellite sensors in capturing data on hydroclimatic processes to describe conditions favorable for emergence of the vectors in historically disease free regions. We propose the hypothesis that an increase in surface temperature (as proxy of warming weather), in combination with intensification of vegetation as a result of enhanced precipitation, lead to conditions favorable for vector growth. Analysis of Land Surface Temperature (LST) pattern shows that temperature values greater than 160C, with heavy precipitation, may lead to abundance of the mosquito population. This hypothesis was tested in West Virginia where a sudden epidemic of WNV infection was reported in 2012. Our results emphasize the value of hydroclimatic processes estimated by satellite remote sensing, as well as continued environmental surveillance of mosquitoes, because when a vector borne infection like WNV is discovered in contiguous regions, the risk of spread of WNV mosquitoes increase at points where appropriate hydroclimatic processes intersect with the vector niche.